Study on Different Human Emotions Using Back Propag ation Method - Subhashree Behera; Pranati Mishra; Amit Tripathy; Himansu Mohan Padhy (International Journal of Innovations in Engineering Research and Technology, 2021)
With fast evolving technology, Cognitive Science plays a vital role in our day-to-day life. Cognitive science is summed up as the study of mind based on scientific methods. It is al l about the sum of all interdisciplinary like philosophy, psychology, linguistics, artificial intelligence, robot ics, and neuroscience. In this paper, I focused on the facial expressions or emotions of human being as it has an impor tant role in interpersonal relations. Without verb communication, one can imagine the mood of a person by expressions. In this method, we use back propagation neural network for implementation. It is an information proce ssing system that has been developed as a generalization of the mathematical model of human recognition.